THE EFFECT OF BIOLOKA BIOFERTILIZER CONCENTRATION THROUGH SPRAYING ON THE GROWTH AND YIELD OF FIVE VARIETIES OF ORNAMENTAL CHILI ( CAPSICUM ANNUUM L. ) - Aiva Viforit; Prastika (Jurnal Penelitian Progresif, 2026)
This study examined the effect of Bioloka biofertilizer concentration (0 ml/L as control and 10 ml/L) through spraying on the growth and yield of five varieties of ornamental chili ( Capsicum annuum L. ): Syakira, Ayesha, Nazla, Viola, and Violeta . The study was conducted in Cinta Damai Village, Bambel District, Southeast Aceh Regency, from August to December 2025, using a 2x5 factorial Randomized Block Design (RBD) with three replications. Seedlings were sown for 21 days until they had 4-6 leaves, then transferred to 15 cm pots with soil, compost, and rice husk charcoal (1:1:1) media. Bioloka spray treatment was given weekly 7 times (20 ml/plant), with observation parameters including plant height (15, 30, 45, 60 HST), stem diameter, and flowering age. Analysis of variance showed significant to highly significant effects on most parameters, such as plant height (F=11.162 at 15 DAP), stem diameter (except at 30 DAP, F=2.095), and flowering age (F=24.481). 10 ml/L Bioloka concentrate significantly increased vegetative growth and flowering through natural hormones, supporting sustainable ornamental chili cultivation by reducing dependence on chemical fertilizers.